Oral health literacy: effectiveness of a homegrown intervention among community-dwelling older Nigerians - B. O. Akinboboye; B. I. Malomo; C. A. Gbiri; A. O. Ogunyemi; A. P. Arikawe; O. A. Obashoro-John (BMC Oral Health)
Abstract Background Health literacy involves the use of acquired health information in taking appropriate steps to improve health status and quality of life. It has a strong association with oral health and is a determinant of overall health. This study explored oral health literacy and determined the efficacy of a home-grown intervention program on health literacy and well-being in older adults in Lagos state, Nigeria. Methods A multi-stage and multi-phased mixed-method study was conducted among adults ≥50 years with a Charlson comorbidity index score ≤ 1. Phase 1 involved a multi-stage sampling in selecting 6 LGAs from ten LGAs within 10kms radius of Lagos University Teaching Hospital. Two wards were randomly selected from each of the 6 LGAs. Participants from visited households were administered the original version (Cronbach’s alpha = 0.67, confidence interval CI = 0.50 to 0.80) and the Yoruba cross-culturally adapted (Cronbach’s alpha = 0.74) adapted 14-item oral health literacy questionnaire (HeLD 14 - item). Each item of the HeLD 14-item scored 0.5 for Yes responses and 0 for No responses. A maximum score < 4 was considered as low oral health literacy. Phase 2 involved random allocation of participants with low oral health literacy into three groups- 2 interventional groups (Health Belief & Motivation Interview) and one control group. Assessment of interventions was made by determining the proportion of participants taking action (trigger) to have dental assessment and treatment. Phase 3 was a Focus Group Discussion (FGD) of twenty participants selected from the three randomly allocated groups participating in a 40-minute focus group discussion on oral literacy and oral health for thematic analysis. Data was analyzed using Pearson Correlation Coefficient Chi-Square, and the Analysis and level of significance were set at P ≤ 0.05. Discussion A total of 481 respondents. Females made up 67.8% of them. The mean age was 68.91 ± 8.36, with most (45.5%) of them in the 61 to 70 years age group. The majority (45.5%) of the participants were between 61 years and 70 years. There was poor oral health literacy among community-dwelling older adults in Lagos State, Nigeria. The home-grown intervention program based on the health belief theoretical framework is an effective approach to improving oral health literacy in older adults. Trial registration This was retrospectively registered at the Pan African Clinical Trial Registry (www.pactr.samrc.ac.za) on the 16th of August 2024.